2007
DOI: 10.1007/s00334-007-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

Conserving idealized landscapes: past history, public perception and future management in the New Forest (UK)

Abstract: The New Forest is one of the most visited regions of Britain. It has recently been designated a National Park in recognition of its unique wood pasture ecosystems, a traditional land-use system, its magnificent scenery and recreational potential, and its biodiversity importance. The Forest's highly prized Ancient and Ornamental (A&O) woodlands are a result of complex interactions among human activities of several kinds and the ecology of the dominant species-beech and oak-under the climate conditions of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Oak comprises the highest percentage of broadleaved woodland in Great Britain but its yield is expected to decline in the south and east under future climate projections (Broadmeadow et al 2005). These forests possess a high economic and socio-economic value (Evans 1984, Grant & Edwards 2008, raising the question as to whether replacement with another oak species, better adapted to summer drought and wet winters, is an appropriate response to projected climate change. While Quercus species are believed to show high competitiveness under drier conditions than currently experienced in southern England (Abrams 1990, Broadmeadow et al 2005, Eilmann et al 2006, Thomas et al (2002) found that a combination of waterlogging in winter and summer drought weakens oak to a level where diseases can attack more readily.…”
mentioning
confidence: 99%
“…Oak comprises the highest percentage of broadleaved woodland in Great Britain but its yield is expected to decline in the south and east under future climate projections (Broadmeadow et al 2005). These forests possess a high economic and socio-economic value (Evans 1984, Grant & Edwards 2008, raising the question as to whether replacement with another oak species, better adapted to summer drought and wet winters, is an appropriate response to projected climate change. While Quercus species are believed to show high competitiveness under drier conditions than currently experienced in southern England (Abrams 1990, Broadmeadow et al 2005, Eilmann et al 2006, Thomas et al (2002) found that a combination of waterlogging in winter and summer drought weakens oak to a level where diseases can attack more readily.…”
mentioning
confidence: 99%
“…In a text written in the late 1700s, the author says hogs were taken "especially among the oaks and beeches" of a wood pasture and open forest area of the New Forest called Boldrewood during the pannage season [45], indicating that the nuts of both tree species were used as pig fodder at the time. The relative importance of the two different trees is not certain for medieval wood pasture, but according to pollen records, oak was much more dominant until the last 200-300 years in the New Forest [46,47].…”
Section: Medieval Pig Feeding On Acorns and Beechnutsmentioning
confidence: 99%
“…To be maintained in the longer term, it must undergo a managed regeneration cycle that will inevitably alter current conditions over the decades to come. Knowledge of the past cultural and environmental conditions that have led to the development of the current system can inform current management choices and provide a temporal perspective on the key question of whether long-term sustainability of this landscape and ecosystem is truly achievable (see Grant and Edwards (2008) for more details).…”
Section: Science Highlights: Integrative Paleosciencementioning
confidence: 99%
“…More detailed accounts of the pollen data can be found in Grant and Edwards (2008) and Grant et al (2009); the pollen data will be deposited with the European pollen database (www. europeanpollendatabase.net/) in due course and, until then, are available from M.J. Grant upon request.…”
Section: Datamentioning
confidence: 99%